1996
DOI: 10.1002/elps.1150171210
|View full text |Cite
|
Sign up to set email alerts
|

The use of elevated column temperature to extend DNA sequencing read lengths in capillary electrophoresis with replaceable polymer matrices

Abstract: Capillary electrophoresis with a replaceable linear polyacrylamide matrix operated at elevated column temperatures of 55 degrees and 60 degrees C was used to extend the separation of DNA sequencing fragments to lengths greater than 800 bases. A solid-state heater was employed to provide stable, uniform temperature control over a significant portion of the capillary. The polymer matrix, 3% w/v linear polyacrylamide in a denaturing buffer, was replaced in the capillary after each run. Using dye-labeled primers a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0
2

Year Published

1999
1999
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 24 publications
3
48
0
2
Order By: Relevance
“…It has been shown by Dovichi and co-workers [52] and Karger and co-workers [53] that elevated temperature increased the read length in DNA sequencing by CE using LPA as a separation medium [51]. In the same way, it is observed that the sequencing size limit increased with higher temperatures using quasi-IPN/GNPs-2 as matrices (Figs.…”
Section: Influence Of Temperaturementioning
confidence: 57%
“…It has been shown by Dovichi and co-workers [52] and Karger and co-workers [53] that elevated temperature increased the read length in DNA sequencing by CE using LPA as a separation medium [51]. In the same way, it is observed that the sequencing size limit increased with higher temperatures using quasi-IPN/GNPs-2 as matrices (Figs.…”
Section: Influence Of Temperaturementioning
confidence: 57%
“…The remaining substitution, insertion, and deletion errors were mostly made in the low resolution regions past 600 bases. The compressions can be eliminated by running the sequencing separations at higher temperatures [12,13,33] or by using alternate chemistries such as replacing guanine with inosine in the sequencing reactions. The use of elevated temperatures for DNA sequencing also results in improved resolution for longer fragments [33].…”
Section: Resultsmentioning
confidence: 99%
“…The elevated temperature has two other positive effects on the analysis time. The electrophoretic mobility increases due to lower viscosity and a higher electric field strength can be applied without risk of the separation selectivity loss, since thermal energy protects molecular stretching of DNA fragments [45,46]. Moreover, capillaries can easily be flushed with higher concentration separation media at elevated temperatures.…”
Section: Theorymentioning
confidence: 99%